Predicting factors of readiness for hospital discharge among hospitalized cancer patients receiving chemotherapy at Maharaj Nakorn Chiang Mai Hospital - Suwan, Panadda; Boonyong, Smakom; Somana, Puttachat; Bourchum, Ubon; Yotchai, Busarapan; Sunpakaew, Nittaya; Bunyoo, Nongnuch (Biomedical Sciences and Clinical Medicine, 2016)
Objective The purpose of this correlation predictive study were to examine the readiness for hospital discharge in patient receiving chemotherapy at Maharaj Nakorn Chiang Mai hospital. Methods The sample comprised 130 patients receiving chemotherapy at Maharaj Nakron Chiang Mai. Data collection was performed December 2014 to February 2015. The research instruments were demographic questionnaire, (The Quality of Discharge Teaching Scale (QDTS), The Care Coordination Scale: CCS and The Readiness for Hospital Discharge Scale: RHDS. The data were statically analyzed using descriptive statistics, Pearson’s product moment correlation, and stepwise multiple regression Results The study revealed that the sample had high level of readiness for hospital discharge (mean =8.59, SD. =1.46), good Quality of Discharge Teaching (mean =8.58, SD. = 1.49) and good The Readiness for Hospital Discharge (mean =4.37, SD. =0.53). There was a significantly positive relationship between readiness for Hospital Discharge and Quality of Discharge Teaching, with the Correlation coefficients of (p < 0.001) respectively. Readiness for hospital discharge accounted for the variance explained in Quality of Discharge Teaching 19.3% (p < 0.001). Conclusion The study results have implications for nurses and other healthcare providers in regards to the development of readiness for hospital discharge intervention and promotion of the Quality of Discharge Teaching. In addition, the results provide patients with adequate information that could enhance their readiness for hospital discharge and continuing care.